Recent advancement and assessment of green hydrogen production technologies - Zainal B.S.; Ker P.J.; Mohamed H.; Ong H.C.; Fattah I.M.R.; Rahman S.M.A.; Nghiem L.D.; Mahlia T.M.I. (Elsevier Ltd, 2025)
Hydrogen energy has garnered substantial support from industry, government, and the public, positioning it as a pivotal future fuel source. However, its commercial realisation faces significant hurdles, including slow infrastructure growth and the high cost of producing clean hydrogen. This review uniquely emphasises the different colour codes of hydrogen, which have been rarely discussed in the literature to date. Hydrogen production methods are classified by colour codes, with green hydrogen, produced from renewable sources such as wind and solar, being the most desirable option. The demand for green hydrogen across various sectors is expected to surge. This review comprehensively evaluates the major hydrogen production methods based on cost, environmental impact, and technological maturity. Recent data confirm the increased efficiency, cost-competitiveness, and scalability of green hydrogen production technologies. The cost of green hydrogen has declined significantly, making it competitive with blue hydrogen (produced from fossil fuels with carbon capture). The review also scrutinises several recent hydrogen production technologies, highlighting their advantages, disadvantages, and technological readiness. Among these, the solid oxide electrolysis cell (SOEC) currently outperforms others, with anion exchange membrane (AEM) and electrified steam methane reforming (ESMR) also showing promise. This review also succinctly summarises global progress in hydrogen infrastructure and policies. By spotlighting the diverse colour codes of hydrogen and discussing the crucial takeaways and implications for the future, this review offers a comprehensive overview of the hydrogen energy landscape. This unique focus enriches the literature and enhances our understanding of hydrogen as a promising energy source. ? 2023 Elsevier Ltd